Biochar Enhances Nitrous Oxide Reduction in Acidic but Not in Near-Neutral pH Soil - Pereira, Engil Isadora Pujol; Lechat, Jerome; Conz, Rafaela Feola; Cardoso, Abmael da Silva [UNESP]; Six, Johan (Mdpi, 2019)
We quantified nitrous oxide (N2O) fluxes and total denitrification (N2O + N-2) in an acidic (Ferralsol) and a near-neutral pH soil (Cambisol) to determine whether biochar's alkalinization effect could be the mechanism inducing potential reductions in N2O fluxes. In Ferralsol, decreases in N2O emissions and in the N2O to N2O + N-2 ratio were observed in both biochar and lime treatments. In Cambisol, neither biochar nor lime decreased N2O emissions, despite significantly increasing soil pH. The abundance and community structure of nosZ gene-bearing microorganisms indicated that gene abundances did not explain biochar effects, but a higher diversity of nosZ gene-bearing microorganisms correlated to lower total denitrification. Overall, our results suggest that biochar's potential to decrease N2O emissions, through soil alkalinization, may be more effective in acidic soils.
Keywords: amendments; denitrification; qPCR; T-RFLP; Ferralsol; Cambisol